Recent Advances on Single‐Atom Catalysts for CO2 Reduction. Issue 3 (27th October 2022) - Liu, Lizhen; Li, Mingtao; Chen, Fang; Huang, Hongwei
Abstract : Continuous consumption of fossil energy and excessive CO2 emission severely restrict human society. Sustainable carbon cycle is a promising technology to simultaneously relieve greenhouse effect and energy crisis based on electrocatalysis and photocatalysis. However, the energy conversion efficiency is confined by the poor carriers utilization and insufficient reactive sites. Single‐atom catalysts (SACs) display outstanding performance in effectively overcoming the aforementioned problems. Herein, recent advances of SACs for enhancing the efficiency, selectivity, and long‐range stability of CO2 reduction are provided. First, the characteristics of SACs have been introduced in detail to provide rational design for SACs based on the relationship between structure and performance, including type, structure, and synthesis of SACs. Then, the high performance of SACs in electrocatalytic, photocatalytic, and thermocatalytic CO2 reduction has been discussed for disclosing reaction mechanism, such as charge transfer, activation barriers, and reaction pathway. In particular, the strategies of enhancing CO2 reduction performance have been summarized to provide deep insight into designing and developing more efficient SACs. Finally, an outlook on the current challenges and perspectives of SACs for electrocatalytic, photocatalytic, and thermocatalytic CO2 reduction is proposed. This review aims to provide a systematic reference for developing SACs in advanced CO2 catalytic conversion. Abstract : This review summarizes the research progress of single‐atom catalysts (SACs) for electrocatalytic, photocatalytic, and thermocatalytic CO2 reduction, and the strategies of upgrading CO2 reduction performance. The type, structure, and synthesis of SACs are introduced, and the current challenges and future prospects are provided, with the purpose for presenting a deep insight and guideline for future researches to wards SACs.